(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
This paper uses a combination of alginate impression and body surface tracing to study the skin deformation mechanism of upper limbs in alpine skiing, and the sleeve pieces were divided into 5 regions combined with the characteristics of human heat and sweat. The thickness, permeability and constant elongation of 7 kinds of elastic fabrics commonly used in tight sports clothing were tested to provide a quantitative basis for fabric compatibility in different zones. The results showed that the skin deformation in the elbow joint area was significant, the transverse changes were mostly stretching, and the longitudinal changes were mostly contraction; the characteristics of heat and sweat in upper limbs were distinct, which could be divided into shoulders, upper arms and below the elbow joint; the order of fabric permeability is as follows: 6>3>7>4>1>2>5, the order of warp tensile elastic modulus is as follows: 7>6>1>5>2>4, the order of weft tensile elastic modulus is as follows: 1>3>7>6>5>2>4; the abc zones of the sleeve are dominated by the demand for air permeability, which is compatible with 3#, 7# and 6# fabrics respectively, the de zones are dominated by the demand for tensile elasticity, which is compatible with 4# and 2# fabrics respectively.